EFFICACY OF 2% BLEACHING POWDER IN CONTROLLING SECONDARYCONTAMINATION OF PEBRINE DISEASE INTASAR SILKWORM ANTHEREAE MYLITTA DRURY (DABA T.V) - LAKSHMI VELIDE (International Journal of Pharma and Bio Sciences, 2013)
Pebrinedisease found to be highly virulent and harm the larval and cocoon characters of tropical tasar silkworm Antheraeamylitta Drury (Daba TV).Therefore an attempt has been made to evaluate the effect of 2% bleaching powder solution in controlling the pebrine disease attained through secondary contamination by studying larval and cocoon characters. In comparison with the healthy control (T1 batch larvae reared on untreated plantation),the results reveal a significant decrease in larval span,larvalweight,number of cocoons harvested, effective rate of rearing,cocoonweight,shellweight,shellratio,filament length, reelability, weight of silkreeled, length of shell, width of shell, shell thickness, peduncle thickness, peduncle length, peduncle weight, peduncle diameter in T2 batch (infected larvae reared on untreated Terminaliaarjuna plants) but a slight decrease was observed in T3 batch (healthy and infected larvae reared combined on 2% bleaching powder solution treated plantation).The results also show that maximum mortality in T1 batch and T3 batch larvae was due to viral and bacterial infections and other factors rather than pebrine disease whereas in case of T2 batch nearly 50% of larval mortality was due to pebrinedisease.Based on the results obtained from present study 2% bleaching powder solution is found efficient in controlling pebrine disease attained through secondary contamination in Daba TV.